Legal Issues in Small-Scale Land Procurement for Low-Cost Rental Apartments in Jakarta - Pranatia, Maria; ., Gunanegara; Gunadi, Anne; Yovinka, Revianty; Budianto, Agus; Arianto, Radityo Fajar (Journal of Cultural Analysis and Social Change, 2026)
This study critically explores the planning and preparatory stages of small-scale land procurement for low-cost rental apartments (Rusunawa) in Jakarta, Indonesia. Although the legal framework under Law No. 2 of 2012, as amended by Law No. 11 of 2020 and Law No. 6 of 2023, regulates land procurement for public purposes, significant gaps remain for projects involving less than 5 hectares. Using a qualitative approach, the research applies focus group discussions and in-depth interviews with government officials, developers, and community representatives to identify challenges in practice. The findings highlight three persistent problems: the absence of technical guidelines following the revocation of Jakarta’s gubernatorial regulation, frequent delays in compensation payments, and additional informal requirements that often trigger disputes. Moreover, inconsistencies between fair and market land values, combined with procedural ambiguities, exacerbate conflicts and delay implementation. The study concludes that establishing a standardized operating procedure (SOP) and service level agreement (SLA) is essential to ensure transparent, effective, and legally compliant processes. Practical recommendations are proposed to assist the Jakarta Provincial Government and other metropolitan areas in formulating actionable SOPs, thereby reducing legal uncertainties and supporting the long-term sustainability of public housing development for low-income communities.